Increase in Plasma Oxidized Phosphatidylcholines (OxPCs) in Patients Presenting With ST-Elevation Myocardial Infarction (STEMI) - Solati, Zahra; Surendran, Arun; Edel, Andrea; Roznik, Marynia; Allen, David; Ravandi, Amir (Frontiers in Medicine, 2021)
Objective: Despite successful reperfusion using percutaneous coronary intervention (PCI), a large percentage of myocardial cells die as a result of ischemia/reperfusion injury (I/R). Changes in Oxidized phosphatidylcholines (OxPCs) which result in cardiomyocyte cell death are investigated in patients undergoing Primary PCI. Samples collected from patients presenting with STEMI at prior to primary PCI (PPCI) (Isch), 2h (R-2h), 24h (R-24h), 48h (R-48h), and 30 days (R-30d) underwent High-performance lipid chromatography-electrospray mass spectrometry (LC-MS/MS) for OxPCs analysis. Total levels of OxPCs did not significantly differ between Isch and control groups. However, fragmented OxPCs are significantly elevated in the Isch compared with controls (Isch: 4.79±0.94, Control: 1.69±0.19 ng/μl of plasma, P<0.05). Concentrations of non-fragmented OxPCs are significantly lower in Isch compared to the control (4.84±0.30 vs 6.6±0.51ng/μl, p<0.05). Fragmented OxPCs were significantly elevated at 48h post-reperfusion. Fragmented OxPC showed a significant decrease at 30 days following MI, when compared to R-2h and R-24h time points (Isch: 4.79±0.94, R-2h: 5.33±1.17, R-24h: 5.20±1.1, R-48h: 4.18±1.07, R-30d: 1.87±0.31 ng/μl, P<0.05). Plasma levels of two fragmented OxPCs:POVPC and PONPC were elevated significantly elevated during reperfusion in STEMI patients were also significantly correlated with peak creatine kinase (CK) levels (P<0.05). Conclusion: Given that fragmented OxPCs are potent stimulators for cardiomyocyte cell death, therapeutics attenuating their activities can result in a novel therapeutic pathway for myocardial salvage for patients undergoing reperfusion therapy.